2016
DOI: 10.18632/oncotarget.13689
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant fluoxetine induces necrosis by energy depletion and mitochondrial calcium overload

Abstract: Selective Serotonin Reuptake Inhibitor antidepressants, such as fluoxetine (Prozac), have been shown to induce cell death in cancer cells, paving the way for their potential use as cancer therapy. These compounds are able to increase cytosolic calcium concentration ([Ca2+]cyt), but the involved mechanisms and their physiological consequences are still not well understood. Here, we show that fluoxetine induces an increase in [Ca2+]cyt by emptying the endoplasmic reticulum (ER) through the translocon, an ER Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Interestingly, in another study where the effect of fluoxetine was studied on non-GBM cancer cell lines, mitochondrial calcium overload and cell death were explained by a completely different mechanism [127]. The effects were observed after exposure to 100 µM of fluoxetine, a clearly supra-pharmacologic concentration.…”
Section: Antidepressants and Glioblastoma Multiforme Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in another study where the effect of fluoxetine was studied on non-GBM cancer cell lines, mitochondrial calcium overload and cell death were explained by a completely different mechanism [127]. The effects were observed after exposure to 100 µM of fluoxetine, a clearly supra-pharmacologic concentration.…”
Section: Antidepressants and Glioblastoma Multiforme Mitochondriamentioning
confidence: 99%
“…This could reduce ATP production, which is required for maintenance of the low intracellular Ca 2+ concentration. Eventually the increased Ca 2+ load was causing direct damage to the mitochondria and release of pro-apoptotic molecules [127].…”
Section: Antidepressants and Glioblastoma Multiforme Mitochondriamentioning
confidence: 99%
“…CaBPs also increased the intracellular Ca 2+ concentration in MCF-7 cells compared to BPs-treated cells ( Figure S16, Supporting Information), which has been documented to be a cause of programmed cell death. [22] Taken together, these results suggested that CaBPs showed enhanced anticancer bioactivity superior to bare BPs owing to intracellular Ca 2+ overload and the stronger pH-responsive degradation in cancer cells.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, it was not possible to correlate the changes in [IP 1 ] to that of intracellular Ca 2+ release or subsequent changes in [Ca 2+ ] i . It is interesting to note that a recent report from Charles et al demonstrated that real-time increases in IP 3 levels could be monitored using confocal microscopy in HeLa cells transfected with a fusion protein made of the Pleckstrin Homology (PH) domain of PLCδ and enhanced green fluorescent protein (eGFP) [42]. The fusion protein binds to phosphatidylinositol 4, 5-bisphosphate (PIP 2 ) and IP 3 and allows the monitoring of IP 3 localization after PIP 2 cleavage regardless of the PLC isoform [42].…”
Section: Discussionmentioning
confidence: 99%